Effect of Palm-Based Desiccated Coconut Filling on Fat Migration in Filled Chocolates - Chin, Hui Han (2006)
Local ingredients such as desiccated coconut, palm mid-fraction (PMF), and refined, bleached, deodorised palm kernel stearin (RBD PKS) has the potential to be used as filling in chocolates. However, softening and bloom formation on chocolate coating have been major problems. The objectives of this study were to develop desiccated coconut filled chocolate using PMF and RBD PKS as the filling fats, to study the mechanism of fat migration and to determine the effectiveness of chitosan in controlling fat migration. Three formulations of filling containing RBD PKS with different ratio of icing sugar and desiccated coconut (5:1, 2:1, and 1:1) were developed and sensory qualities were evaluated by 80 panelists on hardness, taste (sweetness, coconut flavour) and overall acceptability. The most preferred formulation, 5:1 ratio of icing sugar and desiccated coconut, was used in developing the product. It was latter compared against PMF-desiccated coconut filled chocolate in terms of organoleptic properties (hardness, flavour, melt away and overall acceptability), physical (texture analysis) and shelf life (visual inspection of fat bloom formation) prior to sensory quality assessment on hardness, sweetness, coconut flavour and overall acceptability by 30 panelists against imported similar products. Results showed that PMF-desiccated coconut filled chocolate with maximum penetration force (MPF) of 1516.166.8 g was more accepted in terms of hardness and overall acceptability compared to RBD PKS (MPF: 1860.350.4 g). Shelf life of dark chocolate filled with PMF-desiccated coconut filling was higher (7 weeks) than that with RBD PKS (5 weeks). These products were comparable in terms of sweetness, coconut flavour and overall acceptability with the imported similar products. In determining the mechanism and effect of chitosan on fat migration, untreated and treated sample with different concentrations of chitosan (0.0, 1.0, 3.0 and 5.0%) were stored at 30oC for 3 months. Physical properties (texture analysis, bloom test, solid fat content), chemical analysis (total fat content, fatty acid and triacylglycerol composition) and sensory evaluation (hardness, glossiness) were conducted at week 0, 1, 3, 5, 7, 9, and 11. Fat migration of all the PMF-filled samples showed a rapid increase from filling to coating from 0 to 7 weeks of storage and dropped after week-7. Similar profile was observed for all the RBD PKS-filled chocolates, which reached equilibrium stage after week-5. Both chitosan treated samples for PMF and RBD PKS showed no significant difference (p>0.05) with the control in terms of physicochemical and sensory properties.